The case of Kennedy's bulbospinal amiotrophy: modern diagnostic opportunities - Andrey F. Vasilenko; Maria I. Karpova; Maria V. Shestakova; Yulia V. Putintseva; Olga V. Podobed; Gleb Yu. Novikov; Igor V. Kochetkov (LLC "MEDIAFORMAT", 2023)
Kennedy disease is a rare neuromuscular disease associated with damage of androgen receptor gene and inherited by the X-linked recessive type. Its clinic features is characterized by a complex of neurological and extraneural disorders, including extremities peripheral paresis, bulbar syndrome. Some patients also have sensory polyneuropathy, cognitive impairment, endocrine and urological disorders. The article presents a clinical case of a man with Kennedy disease, symptoms debuted at age of 35. The features of the disease were significantly increase the level of blood creatinekinase, the presence of polyneuropathy. The data of a three-year observation of clinical and electromyographic manifestations, the results of laboratory tests, biopsies, and magnetic resonance imaging of muscles are presented. The possibilities of using and features of interpretation of the results of additional examination methods, the difficulties of differential diagnosis of the disease are discussed.